Indonesia National Single Window (INSW) in the Clearance in/out Process of MV. Blue Star at KSOP Class I Tanjung Emas by PT. Kalandara Indah Lautindo Semarang - Ema Sonia Berutu; Syarifur Ridho; Eka Fransiska (Politeknik Pelayaran Sulawesi Utara, 2024)
This research aims to gain a closer understanding of how the Indonesia National Single Window (INSW) operates in the Clearance In/Out process of MV. Blue Star at KSOP Class I Tanjung Emas by PT. Kalandara Indah Lautindo Semarang. The Indonesia National Single Window (INSW) is a nationally integrated electronic system that can be accessed via the internet (public network) and is also automatically integrated directly with Inaportnet. The methods used to obtain data are field research and library research. (library research). In the process of clearance in/out for the MV. Blue Star, PT. Kalandara Indah Lautindo Semarang has been authorized by the owner to manage all the needs of the ship and crew while at Tanjung Emas Port. The clearance in/out process utilizes the INSW system, which is integrated with Inaportnet, and must be coordinated with several agencies such as: the Port Authority, the Port Management Agency Pelindo, Quarantine, Immigration, and Customs. The results obtained from this research indicate that the Indonesia National Single Window (INSW) is already very efficient, particularly in expediting the processing of ship documents to the relevant agencies and does not take much time. However, it still faces obstacles due to the lack of understanding among employees of PT. Kalandara Indah Lautindo Semarang in using INSW. Therefore, it is necessary to participate in socialization efforts to provide input and understanding so that services in the future can improve.